2018
DOI: 10.1155/2018/6986870
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of MUC2 Expression in Colorectal Cancer: A Systematic Review and Meta-Analysis

Abstract: Background The reliability of MUC2 as a prognostic marker in colorectal cancer (CRC) is controversial. This study evaluated the association between MUC2 expression levels in CRC tissues and prognosis. Methods The PubMed, Web of Science, Embase, Cochrane Library, China Biology Medicine disc (CBMdisc), Wanfang Database, and China National Knowledge Infrastructure (CNKI) databases were searched to identify studies exploring the relationship between MUC2 expression in CRC tissues and overall survival (OS). Pooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…Moreover, transcription factors also play different roles in the regulation of MUC gene expression. For example, the Notch/Hath1 axis transcriptionally regulates the expression of MUC6 and MUC5AC genes (Li et al, 2018), while the transcription factors Sp1, SOX9, and CDX2 can participate in the transcriptional regulation of many MUC genes, including MUC2 (Sakai et al, 2005). Furthermore, mutations of tumor suppressor genes, such as p53 and RAS, are involved in the regulation of MUC genes located on chromosome 11p15.5 (Ookawa et al, 2002).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, transcription factors also play different roles in the regulation of MUC gene expression. For example, the Notch/Hath1 axis transcriptionally regulates the expression of MUC6 and MUC5AC genes (Li et al, 2018), while the transcription factors Sp1, SOX9, and CDX2 can participate in the transcriptional regulation of many MUC genes, including MUC2 (Sakai et al, 2005). Furthermore, mutations of tumor suppressor genes, such as p53 and RAS, are involved in the regulation of MUC genes located on chromosome 11p15.5 (Ookawa et al, 2002).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Correlation analysis of MUC expression and clinicopathological parameters of patients with CRC found that MUC2 and MUC5AC were correlated with tumor stage, lymph node metastasis and prognosis of patients, and could be used as biomarkers to evaluate the prognosis of patients (Li et al, 2018), while the overexpression of MUC5B in CRC cells seemed to be related to degree of malignancy (Walsh et al, 2013), and increased expression of MUC6 was associated with malignancy and poor prognosis in CRC cells (Betge et al, 2016). Based on the current findings, the detection of MUC expression in CRC patients will benefit patients in the following aspects.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…MUC6 expression is also reduced in gastric cancers and is an independent predictor for malignant progression . MUC2 is the major structural component of colonic mucosa and has been associated with colorectal cancer, where its reduced expression results in increased inflammation and promotes IL‐6‐induced epithelial to mesenchymal transition …”
Section: Disease Associationsmentioning
confidence: 99%
“…70 MUC2 is the major structural component of colonic mucosa and has been associated with colorectal cancer, where its reduced expression results in increased inflammation and promotes IL-6-induced epithelial to mesenchymal transition. 71 The CA125 antigen is a well-recognised marker for ovarian cancer and corresponds to the cleaved extracellular TR region of MUC16. Mutations of MUC16 have also been associated with air pollution-related lung cancer.…”
Section: Mucins In Epithelial Cancersmentioning
confidence: 99%